Views of academician examiners on the testing accommodations of the measurement, selection and placement center for disabled test takers - Bayram Çetin; Melek Gülşah Şahin; Mustafa İlhan (International Journal of Assessment Tools in Education)
The Measurement, Selection and Placement Center–MSPC (original acronym: Ölçme, Seçme ve Yerleştirme Merkezi–ÖSYM) administers many of the high-stake examinations applied in Türkiye. In order to support equality of opportunity in education and create a fair evaluation system, MSPC actualizes various testing accommodations by adjusting the standardization protocol for disabled test takers. In this research, we examined the views of academicians who served in the halls where disabled candidates take the test in the examinations held by MSPC about the testing accommodations for the disabled. The study design was in the basic qualitative research model. The participants consisted of 12 academicians working at a state university in Türkiye, who had served at least three times in the examination halls reserved for disabled test takers by MSPC. We collected the data via an interview form which included four items and administered it to the participants according to the drop-off and pick-up later method. The research results revealed that academician examiners have various positive opinions about MSPC’s testing accommodations for disabled test takers. However, the participants also expressed that current accommodations have certain limitations that should be revised.